Orient Theme in the Poetry by Valery Bryusov (on the Example of the Literary Work «In the Magic Garden») (Proceedings of Southern Federal University. Philology, 2018)
Tatyana A. Dyachenko (Astrakhan, Russian Federation)This paper is devoted to the images of the Orient poetry in the work by Valery Bryusov. The article describes the oriental images and motives in the literary work «In the Magic Garden». Much attention is given to the motive of «the garden» in the poetic traditions of various cultures (Ancient culture, Renaissance culture and especially Oriental muslim culture) and also to the poetry style at the linguistic level and the level of image. It is specially noted the use of the symbols of the sufi poetry in the literary work by Valery Bryusov.Key words: oriental poetry, image, sufism, nightingale, rose, garden, oriental motive, sufi poetry.DOI 10.23683/1995-0640-2018-4-188-194